Application of ArcGIS and QFD-based model for site selection for bio-medical waste disposal - Jangre, Jogendra (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2022)
With the increasing formalisation of the health sector in India, the bio-medical waste (BMW) disposal regulations are getting stringent and its implementation is being enforced strictly. The coronavirus disease 2019 (COVID-19) created a healthcare crisis because of the highly contagious nature of the novel virus. Measures employed for the prevention and management of COVID-19 resulted in the generation of an unprecedented amount of BMW in Indian medical history. This BMW needs to be disposed of safely at a suitable site to prevent secondary infection and the potential spread of the virus in the environment. The selection of an appropriate site for BMW disposal requires comparing a wide range of social, economic and environmental factors corresponding to different site locations, which makes it a multi-criteria decision-making (MCDM) problem. This study aims to solve the BMW site selection problems using a quality function deployment-based model that can consider both the subjective and the objective criteria, and evaluate them as per the user's requirements. The proposed model is applied to evaluate the suitability of waste disposal sites in the city of Bilaspur in Chhattisgarh, India. At first, eight possible locations for BMW disposal are identified, while utilising geographical information system (GIS). Consequently, the developed model is applied to evaluate the identified sites, taking 18 relevant criteria into consideration. A software prototype is developed in Visual BASIC 6 to automate the entire decision-making process, further adding to the novelty of the work